2022
DOI: 10.1111/liv.15210
|View full text |Cite
|
Sign up to set email alerts
|

Screening and surveillance of oesophageal varices in patients with HCV‐positive liver cirrhosis successfully treated by direct‐acting antiviral agents

Abstract: Background & Aims: limited evidence is available to guide hepatologists regarding endoscopic surveillance of oesophageal varices (EV) in Hepatitis C Virus (HCV)-positive cirrhotic patients achieving a sustained virologic response. To address these issues, we conducted a long-term prospective study on 427 HCV-positive cirrhotic patients successfully treated by Direct Antiviral Agents (DAAs). Methods:Patients were divided into two groups according to their baseline Baveno VI status: Group 1 (92, 21.5%, favourabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Viral suppression and ALT normalisation, leading to reduced intrahepatic inflammation and fibrosis regression, are the most relevant drivers of these favourable findings. Similar data have been recently shown also in DAA‐cured HCV compensated cirrhotics 29,33,34 . Overall, EV disappeared in 17.4% of patients over 3 years 29 …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Viral suppression and ALT normalisation, leading to reduced intrahepatic inflammation and fibrosis regression, are the most relevant drivers of these favourable findings. Similar data have been recently shown also in DAA‐cured HCV compensated cirrhotics 29,33,34 . Overall, EV disappeared in 17.4% of patients over 3 years 29 …”
Section: Discussionsupporting
confidence: 83%
“…Similar data have been recently shown also in DAA-cured HCV compensated cirrhotics. 29,33,34 Overall, EV disappeared in 17.4% of patients over 3 years. 29 Our study provides a unique opportunity to also validate the recent Baveno recommendation in terms of endoscopic surveillance strategy in patients with HBV-related cirrhosis under long-term effective NUC.…”
Section: Discussionmentioning
confidence: 96%
“…While etiological treatment can alleviate PHT, the persistence or worsening of clinically significant PHT in patients with well-known etiology control is not negligible. Previous observational studies have shown that the addition of NSBB can reduce the progression rate of EV in patients with high-risk EV (23,24). However, these findings are based on observational data and lack head-to-head RCT studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, these findings are based on observational data and lack head-to-head RCT studies. The evidence is very limited, particularly for small cases (23,25,26). Our study provides important evidence to further clarify the appropriate use of NSBB in patients with well-controlled etiology.…”
Section: Discussionmentioning
confidence: 99%